The role of governmental and public Palestinian Institutions in elevating the level of competition of Palestinian Athletes in International Sports Competitions - Jayousi, Nader (Πανεπιστήμιο Πελοποννήσου, 2024)
Everything in Palestine speaks politics, from road signs and checkpoints to a separation wall and travel permits. Sports is no different, and in the long struggle for Palestinian freedom against the occupation, it is becoming a battleground for public debate and a tool to promote political agenda using international sporting bodies. This dissertation works to understand “The role of governmental and public Palestinian sports institutions in elevating the level of competition of Palestinian athletes in international sports competitions” It analyses the recent work of the Palestinian Olympic Committee and other Palestinian Sporting organizations in elevating the level of athleticism in Palestine. In addition, the dissertation explores whether appropriate conditions exist in Palestine to use sport as a viable, non-violent, and effective mechanism of change by examining the internal and external barriers limiting its success. And finally, this research assesses the perspectives of Palestinian athletes, coaches, influencers, and stakeholders of Palestinian sport, on the future role of public Palestinian sporting organizations in making real results in international competitions. The study was based on the stories and experiences of individuals who have been involved in sports both in Palestine and internationally; including Palestinian athletes, coaches, international academics, and government officials. The findings show that despite its recency, lack of centralized management, and lack of prioritization in Palestinian political agendas, the role of government can certainly have positive consequences in raising awareness of the growing Palestinian sports movement. Furthermore, the government alone cannot change the outcomes of sporting competitions, but rather it can be one of the many factors Palestine needs to elevate the level of competition of athletes in international sports competitions. In addition, the study finds that policies must be built within the guidelines of a strategic national policy, one that accepts and adopts sports as a viable method of change within the Palestinian community and one that needs focus from a governmental point of view. And lastly, the thesis finds that academic work on the role of government in supporting athletes in Palestine is scarce, hence the study’s findings offer a significant original contribution to the emerging academic literature on Palestinian sport to help unveil the political challenges surrounding and affecting it daily.
Keywords: Αθλητισμός και κράτος - Παλαιστίνη; Ολυμπιακοί αγώνες - Πολιτικές απόψεις - Ιστορία - Παλαιστίνη; Ολυμπιακοί αγώνες - Διοίκηση και οργάνωση - Παλαιστίνη; Sports and state - Palestine; Olympics - Political aspects - History - Palestine; Olympics - Management - Palestine